Domain spillover and job stress: An exploratory study among Nigerian Prison Staff. Issue 3 (3rd July 2022) - Lambert, Eric G.; Otu, Smart; Elechi, O. Oko; Jenkins, Morris; Lanterman, Jennifer L.
ABSTRACT: Prison work is inherently demanding, stressful, and frustrating. The literature supports that work-family conflict (including time-, strain-, behaviour-, and family-based conflict) occurs among prison staff. The psychological strains emanating from these conflicts affect not only staff members' work performance, but also their relationships with family and friends. This study sought to fill gaps in the literature in both practical and theoretical ways by exploring the effects of work-family conflict among 120 Nigerian prison staff. Multivariate regression analysis of survey data indicated that strain- and behaviour-based conflict showed significant, positive effects on job stress; however, time- and family-based conflict did not. Overall, the findings of the current study generally support the assertion that work-family conflict is a job stressor associated with prison staff stress and that strain- and behaviour-based conflict are stressors linked to higher job stress among staff in different nations.